2000
DOI: 10.1128/jb.182.6.1609-1615.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Arginine Biosynthesis in the Bacterial Domain: Novel Gene-Enzyme Relationships from Psychrophilic Moritella Strains ( Vibrionaceae ) and Evolutionary Significance of N -α-Acetyl Ornithinase

Abstract: In the arginine biosynthetic pathway of the vast majority of prokaryotes, the formation of ornithine is catalyzed by an enzyme transferring the acetyl group of N-␣-acetylornithine to glutamate (ornithine acetyltransferase [OATase]) (argJ encoded). Only two exceptions had been reported-the Enterobacteriaceae and Myxococcus xanthus (members of the ␥ and ␦ groups of the class Proteobacteria, respectively)-in which ornithine is produced from N-␣-acetylornithine by a deacylase, acetylornithinase (AOase) (argE encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…In M. abyssi, the OTCaseencoding gene argF was found to be part of a large divergent operon of which the genes identified so far are clustered in the order ECBFGH(A), with argE constituting the left wing of the operon (59). Alignment of OTCase sequences by the Clustal program revealed that M. abyssi argF is clearly homologous to other OTCase genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In M. abyssi, the OTCaseencoding gene argF was found to be part of a large divergent operon of which the genes identified so far are clustered in the order ECBFGH(A), with argE constituting the left wing of the operon (59). Alignment of OTCase sequences by the Clustal program revealed that M. abyssi argF is clearly homologous to other OTCase genes.…”
Section: Resultsmentioning
confidence: 99%
“…Restriction enzymes and T4 ligase were purchased from Boehringer Mannheim and used according to the manufacturer's instructions. The argF gene of M. abyssi strain 2693 (57,59) was amplified by PCR with oligonucleotides 5Ј-GGAATTCCATATGGAAAATTT ATTATCAGTTAAAGATTTA-3Ј (start codon underlined) and 5Ј-CGGGATC CCTACTTTCTTAACTGTTTGTGTC-3Ј to produce NdeI and BamHI restriction sites at the ends of the fragment. The NdeI restriction site was designed to overlap the ATG start codon and the BamHI site after the TAA stop codon.…”
Section: Methodsmentioning
confidence: 99%
“…3). M. abyssi and M. profunda display an unusual structure for the argH gene that codes for the argininosuccinate lyase catalyzing the last step (EC 4.3.2.1) of arginine biosynthesis (82). The argH gene is extended by a 170-codon stretch able to complement an argA E. coli mutant.…”
Section: Substitutes For Classical Nags: Short Nagsmentioning
confidence: 99%
“…The gene is present at the end of an argE/CBFGH(A) operon, where argE-coding for an acetylornithinase (AO)-and the rest of the cluster are expressed divergently, a pattern characteristic of many enteric bacteria. After the original report (82), the argH(A) gene was found in similar genetic contexts in closely related bacteria belonging to the Alteromonas-Vibrio group (81). Two of them-Pseudoalteromonas haloplanktis (46) and Idiomarina loihiensis (36)-do not harbor a genetically identifiable NAGS or OAT (Fig.…”
Section: Substitutes For Classical Nags: Short Nagsmentioning
confidence: 99%
See 1 more Smart Citation